Analisis Pola Konsumsi Makanan Cepat Saji Dan Status Gizi Pada Anak Sekolah Dasar Di Samarinda - Fransiska Novita Sari; Maria Floriana Ping (STIKES Ngesti Waluyo, 2026)
Many communities feel that there is an availability and easy access to fast food. School-age children also have easy access to it because there are many vendors in their neighborhood, and they can order it themselves through applications. This condition risks causing nutritional problems, including being overweight. This study aims to analyze fast-food consumption patterns and the nutritional status in elementary school children in Samarinda. This study used a cross-sectional research design. The sampling technique used was total sampling. Respondents consisted of 94 elementary school students. The research instrument was a fast-food consumption questionnaire. Data were processed using the chi-square statistical test. The results showed that some respondents were overweight (36%) and obese (26%). There was a significant relationship between fast-food consumption patterns and the nutritional status in elementary school children (p=0.000, p<0.05). Health education on balanced nutrition and nutritional status should be implemented early to regulate the eating patterns of school-age children.